Zainab Al-Ghazali’s Interpretation of the Term Qawwam in Surah an-Nisa Verse 34 from a Feminist Tafsir Perspective - Kartika, Widya; Rambe, Uqbatul Khoir (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
The issue of gender equality in the interpretation of the Qur'an remains a subject of debate, particularly in relation to verses that are often interpreted as supporting the superiority of men over women. One of the most controversial verses is Al-Qur'an Surah an-Nisa verse 34 in the phrase qawwam, which is often interpreted as legitimizing male leadership. This study aims to analyze Zainab Al-Ghazali's interpretation of this verse from an Islamic feminist perspective. This study uses a qualitative approach with content analysis of primary sources, namely the Qur'an Surah an-Nisa verse 34 and the interpretation Nadzarat fi Kitabillah by Zainab Al-Ghazali, as well as secondary sources in the form of relevant scientific articles. The results of the study indicate that Zainab interprets qiwamah not as a form of domination, but as a moral and social responsibility that emphasizes protection, justice, and cooperation in the household. She also affirms women's authority in the domestic sphere and their direct spiritual responsibility to Allah. The implications of this research contribute to the development of gender-just exegetical discourse, which can serve as a reference in contemporary Islamic feminist studies and promote more equitable and harmonious family relations among Muslims.